1992
DOI: 10.1088/0964-1726/1/2/004
|View full text |Cite
|
Sign up to set email alerts
|

Optical fiber Fabry-Perot sensors for smart structures

Abstract: Fiber Fabry-Perot interferometers (FFPIS) utilizing internal mirrors have been developed to sense temperature, strain. acoustic waves and other physical perturbations in structural materials, and have been successfully embedded in composites and in metals. The construction, performance and application of the FFPI sensors to smart structures are described

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 12 publications
0
20
0
1
Order By: Relevance
“…These losses may be addressed technically, by use of additional reference power measurements, for example, but an alternative to intensity measurement is desirable. Interferometry offers a potential alternative, in which the sensing element is a length of fiber between a pair of partially reflecting splices 5 or a pair of matched Bragg gratings. 6 To produce these designs, single-mode fiber rather than conventional multimode POF is required.…”
mentioning
confidence: 99%
“…These losses may be addressed technically, by use of additional reference power measurements, for example, but an alternative to intensity measurement is desirable. Interferometry offers a potential alternative, in which the sensing element is a length of fiber between a pair of partially reflecting splices 5 or a pair of matched Bragg gratings. 6 To produce these designs, single-mode fiber rather than conventional multimode POF is required.…”
mentioning
confidence: 99%
“…For intrinsic sensors, previous work by Lee et al 16 has shown that the addition of coatings to produce stronger reflections from the fibre ends has resulted in lower strength fusion splices when compared to those produced using clean fibre-to-fibre splices 17 . …”
Section: Specific Problems With Fp-based Sensor Constructionmentioning
confidence: 99%
“…where R 1 and R 2 are the reflectance of the reflectors and A is the cavity losses [20]. The strain on the EFPI due to mechanical perturbation is given by:…”
Section: Efpi Sensor and Sinusoidal Strainmentioning
confidence: 99%